HUBUNGAN GENETIK SUBORDO SERPENTES BERDASARKAN GEN ND1 - Chandra Puspita Dewi; Yuliardi Zamroni; Nur Indah Julisaniah (Samota Journal of Biological Sciences, 2025)
The suborder Serpentes comprises a highly diverse group of reptiles commonly known as snakes, characterized by significant morphological, ecological, and behavioral variation. Due to the frequent morphological convergence and environmental adaptation among species, genetic approaches are necessary to clarify their phylogenetic relationships. This study aims to analyze the genetic diversity and infer the evolutionary relationships among selected species within the suborder Serpentes using the mitochondrial gene ND1 (NADH dehydrogenase subunit 1) as a molecular marker. A total of 10 species were analyzed using secondary data obtained from the NCBI Nucleotide database. Sequence alignment was conducted using BioEdit, and phylogenetic analysis was performed with MEGA software employing the UPGMA method and Kimura two-parameter model for genetic distance calculation. The resulting phylogenetic tree showed that species with lower genetic distances tended to cluster together, in accordance with their known taxonomic classifications. Similarity values derived from the genetic distance matrix revealed that species within the same genus had similarity above 90%, species within the same family but different genus showed 80–89% similarity, while species from different families within Serpentes showed similarity ranging from 70–79%. These findings indicate that the ND1 gene serves as an effective molecular marker for assessing genetic relatedness and diversity within Serpentes, and that in silico analysis using secondary genetic data can reliably reflect taxonomic relationships.